Little red riding hood - Southgate, Vera (USA : Ladybird, 1988)
An adaption of the favorite folktale about a little girl who goes through the woods to visit her grandmother and encounters a sly wolf
Primary
Keywords: Fairy tales; Children's stories in English, 1945 -- Texts